Implementation of Irrigation Policy in the Decentralized Government: A Case Study of West Java, Indonesia - DIGDOWISEISO, Kumba; SUGIYANTO, Eko; DJUMADIN, Zainul (Journal of Environmental Management and Tourism; Vol 9 No 3 (2018): JEMT Volume IX Issue 3(27) Summer 2018DO - 10.14505//jemt.v9.3(27).02, 2018)
The damage on irrigation networks has a substantial effect on the declining in the productivity of farming, which further implies the farmers’ welfare. One of the possible causes of such problem is related to the implementation of irrigation policy. This paper tries to analyze existing model and provide the alternative model of irrigation implementation in Indonesia through qualitative approach with a case study on West Java. In general, the existing model of irrigation implementation is still territorial based on government affairs. Therefore, the alternative model should adopt a collaborative one.